Targeting Nosocomial Stenotrophomonas maltophilia With Plant Extracts: A Combined Antimicrobial, Antibiofilm and Molecular Docking Study - Akkaya, Yuksel; Erdin, Begum Nalca; Senol, Feray Ferda; Altunova, Haki; Toraman, Zulal Asci; Kilic, Ibrahim Halil (Imr Press, 2025)
Background and Objective: Currently, there is a need for alternative antimicrobial and anti-biofilm strategies owing to the combined challenges of multidrug resistance and biofilm formation by Stenotrophomonas maltophilia. Thus, this study aimed to investigate the antibacterial and antibiofilm effects of extracts from Thymus serpyllum, Mentha piperita, Rosmarinus officinalis, Tilia cordata, Salvia officinalis, and Thymbra spicata against S. maltophilia, as well as the interactions of carnosic acid, luteolin, and carnosol compounds in these extracts with potential target molecules.Materials and Methods: Plant extracts were obtained using a Soxhlet device. Antimicrobial activity against 16 clinical S. maltophilia isolates was evaluated using the disk diffusion method, and the antibiofilm effect was assessed using the microtiter plate method. Carnosic acid, luteolin, and carnosol compounds in the extracts were selected as ligands, and a binding analysis was performed with proteins.Results: The T. serpyllum extract showed the highest inhibition zone (20.5 +/- 2.8 mm; p < 0.005), with dose-dependent antimicrobial activity (1024 mu g/mL > 512 mu g/mL; p < 0.05). Among the assessed 15 biofilm-producing strains, T. serpyllum inhibited 10, S. officinalis inhibited six, and R. officinalis inhibited five strains. Molecular docking indicated strong binding energies (carnosic acid: -8.51 kcal/mol, luteolin: -7.62 kcal/mol, carnosol: -9.23 kcal/mol) and multiple interactions with the MlaC protein.Conclusion: These findings suggest that extracts from T. serpyllum, S. officinalis, and R. officinalis may target the Mla pathway and exhibit promising antimicrobial and antibiofilm effects against multidrug-resistant S. maltophilia, likely through the associated active compounds. The molecular docking analyses further supported the potential of these extracts to disrupt membrane integrity by interfering with the Mla system, thereby enhancing bacterial susceptibility to antimicrobial agents. However, additional studies are required to validate these mechanisms and investigate their broader biological implications.
Keywords: Stenotrophomonas maltophilia; Thymus serpyllum; luteolin; biofilms/drug effects; molecular docking simulation